2014
DOI: 10.1055/s-0033-1363758
|View full text |Cite
|
Sign up to set email alerts
|

Does Phosphodiesterase Inhibition Lessen Facial Flap Necrosis in Tobacco Cigarette Users?

Abstract: Tobacco cigarette smoking remains a serious risk factor for necrosis of local facial skin flaps. To date, no pharmacological therapies exist for cigarette smoke-induced impairment of skin flap tissue survival. Accumulating evidence suggest that phosphodiesterase-5 (PDE-5) inhibitor therapy may counteract the negative effects of cigarette smoke on flap survival. Here, we evaluate skin flap survival in a series of consecutive tobacco cigarette users treated with the PDE-5 inhibitor, sildenafil, who underwent loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The dose used was 100 mg/kg, once a day, 30 days before surgery, and 7 days after surgery. 6 Although there are articles showing the improvement of flap circulation in smokers with the use of PDE inhibitors, 13,15 these results should be interpreted with caution, since in practice we observe catastrophic results in skin flaps, even in clinical patients who are healthy and nonsmokers. The orientation to stop smoking 4 weeks before and after the procedure should prevail in clinical-surgical practice.…”
Section: Discussionmentioning
confidence: 98%
“…The dose used was 100 mg/kg, once a day, 30 days before surgery, and 7 days after surgery. 6 Although there are articles showing the improvement of flap circulation in smokers with the use of PDE inhibitors, 13,15 these results should be interpreted with caution, since in practice we observe catastrophic results in skin flaps, even in clinical patients who are healthy and nonsmokers. The orientation to stop smoking 4 weeks before and after the procedure should prevail in clinical-surgical practice.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the clinical application in an empirical way, there are few publications that report the use of five phosphodiesterase inhibitors to improve the skin flap viability [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral, topical, and locally injected PDE5 inhibitors have been demonstrated to increase the perfusion and viability of ischemic flaps in rat models. 2 , 3 , 4 , 5 , 6 In 2014, Pfaff et al 7 demonstrated that facial reconstruction with flaps in smokers may have improved clinical outcomes with sildenafil 20 to 50 mg, 1 to 3 times daily for 1 to 7 days, starting on POD 0 or 1.…”
Section: Discussionmentioning
confidence: 99%